Immigration Detention and the Racialized Governance of Illegality in the United Kingdom - Turnbull, Sarah (Social justice, 2017)
The article discusses the alleged racism in Great Britain's detention of immigrants in the country's immigration removal centres (IRCs), within the context of Great Britain's immigration policy. An overview of the race relations between the largely white detention custody officers (DCOs) and the immigrant detainees of color is provided.